2003
DOI: 10.1080/01913120309926
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Corpuscle-Like Bodies in Colonic Mucosa

Abstract: During the routine examination of a segment of colon resected for adenocarcinoma, a diffuse proliferation of mucosal tactile corpuscle-like bodies was identified. The bodies showed a lamellar structure by light microscopy and were S-100 positive. Electron microscopy demonstrated parallel slender processes with prominent surface caveolae, arising from peripheral cell bodies. Similar structures sometimes occur in neurofibromas but they have not previously been reported in the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 0 publications
4
31
1
Order By: Relevance
“…3 The hypotheses on this lesion are various as reactive, neoplastic, or amartomatous. 1 The reactive nature of the proliferation was supposed because the first 2 cases described at gastric and colonic level were associated with the presence of an adenocarcinoma 4,5 ; this hypothesis was not confirmed in subsequent and more numerous observations, 1-3 as in our case, where these corpuscles were present in the normal context of gastric or colonic mucosa.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…3 The hypotheses on this lesion are various as reactive, neoplastic, or amartomatous. 1 The reactive nature of the proliferation was supposed because the first 2 cases described at gastric and colonic level were associated with the presence of an adenocarcinoma 4,5 ; this hypothesis was not confirmed in subsequent and more numerous observations, 1-3 as in our case, where these corpuscles were present in the normal context of gastric or colonic mucosa.…”
Section: Discussioncontrasting
confidence: 75%
“…The majority were observed in the colon and rectum. 1,[3][4][5] Here, we report a case of Wagner-Meissner-like corpuscles detected in gastric mucosa biopsy specimens and literature review.…”
Section: Introductionmentioning
confidence: 99%
“…Whether TCLB is reparative or neoplastic remains unclear: the first 2 reported cases could suggest a relationship of TCLB with neoplasia 7,8 ; however, that association would seem coincidental with experience with additional examples. Some observers have suggested that these structures in the GI mucosa might represent part of the morphologic spectrum of Schwann cell hamartoma, 17 which, like TCLB, is an incidental finding of no real clinical significance.…”
Section: Discussionmentioning
confidence: 70%
“…3,11 Nonsyndromic TCLBs have been described only rarely in the GI tract-type mucosa. The initial description was by Wills et al, 8 who reported an incidental colonic In the present study, we analyzed a series of 9 TCLB cases identified as incidental findings. On the basis of the literature and the 9 cases presented herein, TCLB always arise in the lamina propria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation